Confucian culture: the scapegoat of Chinese EFL students’ unwillingness to communicate - Feng, Xia Yu; Bee, Eng Wong (Penerbit Universiti Kebangsaan Malaysia, 2025)
It is a stereotype and misconception that Confucian culture is generally viewed as the dominant factor resulting in Chinese EFL students’ weak Willingness to Communicate (WTC) in class. First, Confucian culture has been misconstrued as respecting teachers’ authority by suppressing one's own opinions. Second, it is an exaggeration to characterise and label all Chinese students as followers of Confucian cultural values. No study has yet surveyed Chinese EFL college students’ identity formed from Confucian cultural values and their influence on their WTC. In this study, a questionnaire was administered to Chinese EFL college students to survey their identity formed from Confucian cultural values and explore the relationship between the identity formed from Confucian cultural values and Second Language (L2) WTC. Surprisingly, the result demonstrates that the majority of students only hold a weak identity formed from Confucian cultural values. Even more surprising, Confucian cultural identity and Chinese EFL students’ L2WTC have a weak positive correlation. This finding indicates that a stronger identity formed from Confucian cultural values won’t result in weaker L2WTC; conversely, a strong identity formed from Confucian cultural values may contribute to a strong L2WTC. Furthermore, the stronger influencing factor of L2WTC is being unable to speak due to the lack of vocabulary or language knowledge. Finally, in order to break the stereotype, an attempt is made to propose a Complex Dynamic System (CDS) insight for Confucian cultural influence on EFL students’ L2WTC, based on the CDS principles of Second Language Acquisition (SLA).